2019
DOI: 10.1128/jvi.01687-19
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Ebola Virus VP24 Protein by SUMO

Abstract: Some viruses take advantage of conjugation of ubiquitin or ubiquitin-like proteins to enhance their own replication. One example is Ebola virus, which has evolved strategies to utilize these modification pathways to regulate the viral proteins VP40 and VP35 and to counteract the host defenses. Here, we show a novel mechanism by which Ebola virus exploits the ubiquitin and SUMO pathways. Our data reveal that minor matrix protein VP24 of Ebola virus is a bona fide SUMO target. Analysis of a SUMOylation-defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Next, we hypothesized that VP24 lipid-binding may be more dependent on mammalian cell expression due to potential post-translational modifications (PTMs) that may alter VP24–lipid interactions. For instance, VP24 is known to undergo SUMOylation that covalently attaches the small ubiquitin-like modifier (SUMO) to the target protein [ 39 ]. Thus, HEK293 cells were transfected with plasmids of HA-tagged VP24 (HA-VP24) or enhanced green fluorescent protein (EGFP)-tagged lactadherin C2 domain (LactC2) (LactC2-EGFP) which is a well-established PS binding protein [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we hypothesized that VP24 lipid-binding may be more dependent on mammalian cell expression due to potential post-translational modifications (PTMs) that may alter VP24–lipid interactions. For instance, VP24 is known to undergo SUMOylation that covalently attaches the small ubiquitin-like modifier (SUMO) to the target protein [ 39 ]. Thus, HEK293 cells were transfected with plasmids of HA-tagged VP24 (HA-VP24) or enhanced green fluorescent protein (EGFP)-tagged lactadherin C2 domain (LactC2) (LactC2-EGFP) which is a well-established PS binding protein [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent study reported that sumoylation of residue K14 of VP24 enhances K binding and IFN antagonistic function (54). In contrast, ubiquitination, including at residue K206 within CL3 (Figure 2A), appears to negatively regulate IFN antagonist activity (54). Intriguingly, K14 is distal to CL1-3 but is within a predicted NES motif (Figure 2A).…”
Section: Discussionmentioning
confidence: 97%
“…NLRP3 [38] Regulates NLRP3 inflammasome activation [38] NF-κB [39], NEMO [33] Regulates NF-κB signaling [33,39] VP24 [49] Involves in virus replication [49] Tat [50] Involves in virus production [50] TRAF3/TRAF6 [51] Modulates antiviral signaling [51] TRAF6/IKKγ [34] Regulates TLR signaling [34] USP-10 CFTR [37,52] Epithelial mucosal clearance [37,52] NICD1 [53] Regulates Notch signaling [53] USP-11 E2F1 [54] Regulates lung epithelia proliferation and wound healing [54] LPA1 [36] Enhances inflammation [36] USP-13 IL-1R8/Sigirr [40] Suppresses lung inflammation [40] PTEN [41] Regulates cell apoptosis [41] MCL1 [42] Regulates transformation of fibroblasts [42] STAT1 [55] Regulates IFN Signaling [55] STING [56] Negatively regulates antiviral responses [56] USP-14 I-kB [31] Increases cytokine release [31] CBP [32] Lung inflammation [32] USP-15 IκBα [57] NF-κB activation [57] USP-17 HDAC2 [58] Reverses glucocorticoid resistance [58] TRAF2/TRAF3 [59] Lung inflammation [59] [92] Inhibits type I IFN signaling and antiviral response [92] POH1 pro-IL-1β [93] Negatively regulates the immune response [93] BRCC3 NLRP3…”
Section: Dubsmentioning
confidence: 99%
“…USP7 (HAUSP)is originally identified as a viral binding protein that preferentially cleaves K11-, K63-and K48-linked ubiquitin chains [119,120]. USP7 is involved in viral infection by targeting virus related protein to modulate virus replication and production [49][50][51]. USP7 is reported to deubiquitinate and stabilize NF-κB to increase its transcriptional activity in TLR-induced inflammatory gene expression [39].…”
Section: Uspsmentioning
confidence: 99%